The optimum time of artificial insemination in Simmental cross cow. Issue 1 (April 2020) - Firmiaty, S; Idrus, M; Amir, M; Toleng, A L
Abstract: Artificial insemination (AI) conducted not at the optimum time might cause the low conception rate in beef cattle kept under extensive and semi extensive conditions. The aim of this research was to evaluate the optimum time of artificial insemination which shows a high conception rate in Simmental cross cows kept under semi extensive condition. There were 75 Simmental cross cows kept under semi extensive by farmers at Bone District, South Sulawesi, Indonesia. They were divided into 3 groups of 25 cows. Group 1 (G1) were inseminated 12 h after the onset of estrus, Group 2 (G2) were inseminated 24 h after the onset of estrus and Group 3 (G3) were inseminated 36 h after the onset of estrus. All cows inseminated using Simmental bulls frozen semen by 1 professional inseminator. The cows returned to estrus after the first AI was served for the second AI. The variables observed were conception rate (CR) and service per conception (S/C). The significant difference between the group was analyzed by chi-square analysis. Conception rate in G1 was significantly (P<0.05) lower (56%) compared to those in G2 (80%) and G3 (80%), respectively. A similar response was detected for S/C. Service per conception in the G1 group was significantly (P<0.05) higher (1.92) compared to those in G2 (1.28) and G3 (1.32), respectively. It can be concluded that optimum time for artificial insemination in Simmental cross breed cows was 24 h after the onset of estrus.